The schooling of the public library, with a proposal to extend the coverage of the official public libraries of Costa Rica to the community - Rodríguez Chaves, Olga (2006)
According to the results obtained by the diagnosis and to reduce the phenomenon of schooling in public libraries studied, drafted a proposal that focuses on the organizational phase, distribution, promotion and evaluation of a new management model based on the development of an information service to the community (SIC).